IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PEMBIASAAN BERBASIS KEARIFAN LOKAL - Hanifatul Husna Hapsari; Syahria Anggita Sakti (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the implementation of character education through local wisdom-based habituation at TK Pertiwi Puro Pakualaman, Yogyakarta. Employing a qualitative descriptive approach, the study involved the school principal, teachers, and students as primary subjects. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicate that character value habituation is not merely a routine activity but a synthesis of daily behavioral ethics and Javanese philosophical values. The internalization of politeness, discipline, and responsibility is achieved through the systematic integration of local wisdom, such as the use of the Javanese Krama language, Karawitan art, and the teachings. These results suggest that utilizing local cultural instruments is effective in transforming normative behavior into deep-rooted character habituation in early childhood.The novelty of this research lies in the utilization of teachings as a specific foundation for character education, distinguishing it from general educational models. While effectively implemented, its success is still hindered by a lack of synchronization between school and home parenting patterns. The implication is that successful local wisdom-based character education requires a systemic synergy between school cultural values and parental involvement to ensure the sustainability of these values in the modern era.